Qualidade na educação pública: um estudo de caso de uma escola municipal de ensino fundamental I de Foz do Iguaçu - Barbosa, Carina Simonetti Colombelli (2019)
In Brazil, access to education is everyone's right, but by itself this guarantee does not imply access to quality education. In a system in which the bourgeoisie dominates the state and largely determines the education system, thinking about democratization and the quality of education requires understanding that the educational system must change so that education is thought of in an equal manner. The present work is a qualitative research that seeks to show different concepts of quality education and also discuss how the democratization of access to education occurred in Brazil and, later, how business ideas came to be applied in education, promoting the dispute and the precariousness of education, seeking results such as productivity in the company and, thus, achieving an alleged quality that is expressed through standardized examinations that claim to measure the quality of education in Brazil, but which may even further enhance its exclusionary character. The discussion of the quality of public education will serve as a theoretical basis for this master's research that is done on a case study in a public school in the municipality of Foz do Iguaçu that serves students from 1st to 5th grade of elementary school, which has its disputed places and is recognized by society as a quality school. This school sought to evaluate the Ideb grade as one of the determining factors in the process of this recognition as a quality school, after all, it presented from 2007 to 2017, a significant increase in the Ideb grade, from 5.8 to 8.3, being among the best in the city. In addition, the privileged physical aspects of the school, geographical positioning, high socioeconomic profile of students and school management were also analyzed. All these points contribute significantly to the results obtained by the school, but research has also shown that other data contribute to raising grades, after all, the practice of student training for large-scale assessments occurs, as well as flow control through failed in the grade before the class that takes the test, grade 4, and in the year after the test, which ends up selecting the students who will take the test the following year.